Penerapan Model Pembelajaran Inside Circle Dalam Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Inpres 7/83 Pacing Kecamatan Awangpone Kabupaten Bone - Makmur Nurdin; Sitti Jauhar; Abu Darwis (Publikasi Pendidikan, 2017)
The problem in this research is the lack of grade IV students’ learning outcome in social study subject. The problem statement in this research is how does the implementation of inside outside circle learning model increase the social study learning outcomes of grade IV students in SD Inpres 7/83 Pacing, Awangpone, District of Bone? The objective of this research is to describe the implementation of inside outside circle learning model in increasing social study learning outcomes of grade IV students in SD Inpres 7/83 Pacing, Awangpone, District of Bone. The benefits of this research consist of theoritical and practical benefits. The research approach used in this research is Classroom Action Research (CAR). The research focus is the implementation of inside outside learning model in increasing the social study learning outcomes of grade IV students in SD Inpres 7/83 Pacing, Awangpone, District of Bone. Setting of the research held in SD Inpres 7/83 Pacing, Awangpone, District of Bone and the subjects are teacher and the grade IV active students in the even semester academic year 2015/2016 with the 16 numbers of students, 7 male students and 9 female students. The research design consists of fours steps starting from planning, applying, observing, and reflecting. The data collection techniques of this research were test and observation. The data analysis techniques used in this research are data reduction, data presentation, conclusion/verification. The result research can be concluded that the implementation of inside outside circle learning model can increase social study learning outcome of grade IV students in SD Inpres 7/83 Pacing, Awangpone, District of Bone. It can be seen from the increase of the percentages of students activity and grade in cycle 1 are in the category of moderate, whereas in cycle II in the category of good.Keywords: learning model, students learning outcome